Unveiling the mutual ion-storage mechanism of dual-carbon NaTFSI-WiSE Cells: A molecular dynamics study. (5th March 2023) - Mendes, Rodrigo A.; Dias, Luis G.; Da Silva, Juarez L.F.; Siqueira, Leonardo J.A.
Abstract: The application of sodium cation in electrochemical devices has been considered an alternative technology for energy storage applications. Water-in-salt electrolyte (WiSE) combined with dual-carbon electrodes can be considered an emerging eco-friendly alternative, however, several problems remain in debate, e.g., what is the ion-storage mechanism? Thus, we carried out molecular dynamics investigations considering three different dual-carbon sodium-WiSE cells at different salt/water concentrations, namely, 4.50, 6.76, and 9.25 mol kg −1 . Furthermore, we employed the constant potential model to simulate the charging behavior of these systems at two potential differences, namely, Δ Ψ = 1 V and 2 V. The best results for the total accumulated charge at 2 V were from the 6.76  m and 9.25  m systems. From the analysis of the evolution of the local charge on the electrodes, we identified a crucial role in the mutual ions migration inside both the positive and negative sides of the dual-carbon. In general, cations are driven into the pores coordinated by water molecules and keep their solvation shell during all the simulation time. Except when they are highly confined into narrow pores, where they have fewer water molecules in their surroundings. Therefore, from our simulations and analyses, the storage mechanisms are associated with sodium adsorption together with H 2 O co-embedding. Graphical abstract: